Topical Application of 0.5% Timolol Maleate Hydrogel for the Treatment of Superficial Infantile Hemangioma - Wu, Hai Wei; Liu, Chao; Wang, Xuan; Zhang, Ling; Yuan, Weien; Zheng, Jia Wei; Su, Li Xin; Fan, Xin Dong (Frontiers in Oncology, 2017)
The therapeutic options for infantile hemangiomas (IHs) have been greatly altered since the introduction of oral propranolol for successful treatments of IHs. Recently, there is an increase in the application of topical timolol maleate for treating superficial IHs. In the present study, we developed a new formulation of timolol maleate 0.5% hydrogel, and treated 321 patients with superficial IHs to evaluate its efficacy and safety in the treatment of superficial IHs. This new timolol hydrogel was applied three times daily with a mean duration of 7.1 months. Response to treatment was assessed according to cosmetic improvement by using visual analogue scale (VAS). The average VAS improvement after treatment was 76.4, with 126 patients (39.3%) achieving excellent responses, 159 patients (49.5%) achieving good responses, 33 patients (10.3%) achieving fair responses and 3 patients (0.9%) achieving poor responses. Age at treatment initiation (P=0.0349) and lesion thickness (P=0.0147) were significantly associated with therapeutic efficacy. No severe side effects were observed in all patients. In conclusion, this new topical timolol maleate 0.5% hydrogel appears to be a proper candidate for treating superficial IHs, and our study provides supportive evidence and experience of topical timolol maleate in treating superficial IHs.